Rising populations without sustainable food systems will heighten Africa’s infectious disease burden - Bett, Bernard K. (2022)
Africa’s unprecedented growth in human population and urbanisation will likely exert more pressure on ecosystems, mainly through the transformation of food systems. These changes would heighten the risk of many infectious diseases, including those shared between humans and animals. Identifying sustainable food production systems in line with the One Health framework is therefore essential to pre-empt future pandemic, epidemic or endemic diseases.